Anger, physical activity and depression in patients with coronary heart disease : a dominance and moderation analysis - Ng, Emil Jin Huai (2015)
Past studies have shown a link between trait anger, physical activity and depressive symptoms. Cardiac patients have also shown an increased likelihood of developing depressive symptoms. This cross-sectional study surveyed 71 patients undergoing community-based cardiac rehabilitation at the Singapore Heart Foundation and obtained a self-report on their average physical activity, depression and trait Anger. Trait anger was measured using an abridged version of the State Trait Anger Expression Inventory 2 (STAXI-2), which consists of 5 different subcomponent scores: (1) Trait Anger, (2) Anger Expression In, (3) Anger Expression Out, (4) Anger Control In, (5) Anger Control Out. Dominance analysis of the STAXI-2 subcomponent scores indicated that Anger Control In, followed by Anger Expression In, were the dominant predictors of depression. A further regression analysis was conducted and found a significant relationship between each of the STAXI-2 components and Depression, but not Physical activity. However physical activity was found to be a significant moderator of the relationship between Anger Expression Out scores and depression. At low levels of physical activity, anger expression has the simple effect of increasing depressive symptoms. However at higher levels of physical activity, the magnitude of the simple effect of anger expression out on depression is greatly reduced. The findings seem to partially support the psychodynamic theory of inward directed anger leading to depression, and also suggest that increasing physical activity may be helpful in reducing the likelihood of depressive outcomes in cardiac patients by moderating the relationship between the propensity to express anger and depression.